2008
DOI: 10.1111/j.1365-2958.2008.06252.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of a cold‐sensitive mutation in ribosomal protein S5 reveals a role for RimJ in ribosome biogenesis

Abstract: SummaryA specific mutation of Escherichia coli ribosomal protein S5, in which glycine is changed to aspartate at position 28 [S5(G28D)], results in cold sensitivity and defects in ribosome biogenesis and translational fidelity. In an attempt to understand the roles of S5 in these essential cellular functions, we selected extragenic suppressors and identified rimJ as a high-copy suppressor of the cold-sensitive phenotype associated with the S5(G28D) mutation. Our studies indicate that RimJ overexpression suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 63 publications
1
53
0
Order By: Relevance
“…As stated above, in earlier work we demonstrated that RimJ, when overexpressed in the S5(G28D) background, mitigated the fidelity errors evident in the S5(G28D) strain (11). Therefore, a role of RimJ in rescuing 16S rRNA processing defects of the S5 (G28D) strain was assessed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As stated above, in earlier work we demonstrated that RimJ, when overexpressed in the S5(G28D) background, mitigated the fidelity errors evident in the S5(G28D) strain (11). Therefore, a role of RimJ in rescuing 16S rRNA processing defects of the S5 (G28D) strain was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…1C). An increase in mature 16S rRNA in 70S ribosomes correlates with increased translational fidelity in the S5(G28D) background, yet RimJ does not associate with translating ribosomes (11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations